Inovação tecnológica : um mapeamento de patentes sobre o uso da nanotecnologia em diagnósticos e tratamentos médicos - Cruz, Cleide Ane Barbosa da (2016)
Nanotechnology is a science that involves the manipulation of atoms and molecules to process perform, building of things and living beings. With the development of studies about this science, it began to explore its use in the medical treatments through of Nanomedicine, which is the application of nanotechnology in the treatment of medical diagnostics. Technology forecasting is a tool that maps scientific and technological advances that assist in the decision-making process. This research aims to map the technological studies on the use of nanotechnology in medical treatments, in order to check the growth of patent applications and gaps in this area in Brazil. Therefore, it performed a technological mapping through of patent databases of the National Institute of Industrial Property (INPI) and European Patent Office (EPO), as well were collected data on the application of nanotechnology studies in medical treatment through the National Institutes of Science and Technology (INCTs). The results showed that in Brazil has increased the number of patent deposits, and this growth has been increasing since 2000. In European basis, it was found that in the last five years analyzed had a leverage from 2013. As for the five INCTs focused on nanotechnology, which have lines of research related to the diagnosis and medical treatment, it was observed that the production of patents directed to nanotechnology directed to medical treatment began in 2009, emphasizing that patents related to treating cancer and other types of treatments appeared with more emphasis on search patents. Thus, through this study, it was found that the studies related to nanotechnology are in development, and through technological mapping was possible to see which technologies on the use of nanotechnology in medical treatments are being created, contributing to its application in the market.